Peace is everyone's business - Ewert, Lowell M.; Bird, Frederick B. 1938- (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"The premise of this book is very simple. While acknowledging that much progress has been made since the end of World War II to improve life conditions for billions of people and reduce the likelihood of war, current global challenges threaten to undermine, undo, or even reverse much of the progress made. Growing political and social polarization, and the resultant increasing fear of each other, is on a trajectory that could cause unprecedented harm. Universities, which have played a pivotal role in creating a more humane and just world that has benefited many through research, teaching and scholarship, now have an opportunity to resist this trajectory by thoughtfully examining how each discipline and vocation can contribute to continue to build peace. The potential crises today are profoundly different in scope and character. Therefore, if universities simply adopt a wait-and-see attitude and continue their work as if it is business-as-usual, the fabric of peace, and the gains that have been achieved, will likely slowly atrophy. Students will also not be adequately prepared as leaders in building a just global order if they are not encouraged and challenged to use their minds actively to think about what is happening in the world and how they can use the skills and knowledge they are acquiring to make a constructive difference. While not every discipline or vocation shares the same level of responsibility to creatively advance peace, all have the potential to do so if they more intentionally and more thoughtfully actively look for avenues to do so. This book, collaboratively developed through conversations with authors from four different university faculties, explores the development of an interdisciplinary framework for the 21st century that may be better able to assist educators prepare their students for the world they will inherit. The book authors approached this manuscript with two overall goals in mind. First, to indicate that everyone can have an impact on peace and that many already do in both constructive (illustrated by many chapters) and negative ways (by not thinking, supporting policies that result in cultural, structural or slow violence). We make this claim in part because we offer an expansive view of peace by promoting human rights, identifying and resolving situations of slow violence, by working to promote fair and sustainable economic development, by identifying and resolving injustices, and by establishing institutions and practices to resolving conflicts by communicative means"-- Provided by publisher.
Keywords: Peace -- Study and teaching (Higher); Education, Higher -- Aims and objectives.; Education -- Teaching -- Subjects -- General.; Teaching of a specific subject.; elektronické knihy; electronic books